Development of Prototypical Indoor Real-time Location System for Medical Equipment Management Based on BLE Devices - Assawasillapakul, Teerawit; Singkhleewon, Nutdanai; Thanasin, Kanlaya; Khambun, Amonrat (วารสารวิจัย มทร. กรุงเทพ, 2023)
Generally, healthcare is considered the fastest growing business and largest service industry in the world. However, hospitals are typically large buildings with various equipment spread over multiple floors. The positioning and tracking of assets in indoor environments have great potential to assist staff in locating needed equipment without wasting time searching for it. Therefore, this research proposes the development of the prototypical indoor real-time location system (RTLS) based on Bluetooth Low-Energy technology devices for any equipment tracking in test scenario. The ESP32 microcontroller is used as the transceiver node in each room to receive the MAC address of the HM-10 beacon attached to the equipment within range and transmit data to a web server. A data filter is applied to reduce noise from Received Signal Strength value for distance between node and beacon calculation. The efficiency test results show that the average distance error between beacon and node is around 3 m, and the maximum duration of location updating from node to node in the scenario is no more than 15 seconds. It can be concluded that if equipment with beacon is in the tracking area of the node, then the presence status of the equipment in each room can be correctly transmitted to the web server.